AB0086 Anti-Citrullinated Protein Antibodies in Patients with Cardiovascular Disease without RA. (15th July 2016) - Van Der Woude, D.; Hermans, M.P.; van der Velden, D.; Trouw, L.A.; Huizinga, T.W.; Kuiper, J.; Schalij, M.J.; Jukema, W.J.; Toes, R.E.
Abstract : Background: Anti-citrullinated protein antibodies (ACPA) are thought to be highly specific for RA. ACPA are associated with risk factors for RA and with joint destruction, and are therefore presumed to be involved in RA pathogenesis. ACPA-positive RA patients also have increased cardiovascular mortality (1). In cardiovascular disease, inflammatory changes occur in vessel walls, raising the question whether ACPA (presumed to be pro-inflammatory) may contribute to this process. Objectives: To investigate the prevalence and prognostic implications of ACPA in patients with cardiovascular disease without RA. Methods: ACPA were determined by anti-CCP3 commercial assay in baseline sera from 290 patients with ST-elevation myocardial infarction participating in the MISSION intervention study (2). Patients with RA were excluded. The association between ACPA and long-term mortality was investigated. Results: 30/290 (10.3%) of the non-RA patients with cardiovascular disease were ACPA-positive. ACPA-positive non-RA patients had a significantly increased long-term cardiac mortality compared to ACPA-negative non-RA patients (Figure ). Corrected for age, ACPA positivity was independently associated with long-term mortality [HR 2.4 (CI 1.1–5.4) p-Value=0.026]. Conclusions: ACPA can be detected in a considerable proportion of non-RA patients with cardiovascular disease. This challenges the presumed specificity of ACPA for RA. In both RA and cardiovascular disease, ACPA are associated with a worse disease outcome possibly by an ACPA-specific enhancement of inflammation. Future studies into ACPA in patients with cardiovascular disease offer the opportunity to dissect which risk factors are associated with ACPA in RA versus non-RA patients. This may supply crucial insights into the development of this autoimmune reaction. References: Humphreys JH et al. Arthritis care & research 2014;66(9):1296–301. Liem et al. American Heart Journal 2007;153(1):11. Disclosure of Interest: None declared